The Jossey-Bass reader on contemporary issues in adult education - Merriam, Sharan B.; Grace, Andre P., 1954-; Jossey-Bass Inc. (San Francisco : Jossey-Bass, 2011)
'This essential resource is compiled by experts in the field and contains the best, most recent previously published literature on the contemporary issues and includes trends affecting adult education. Compelling to practitioners in the field as well as useful in foundations or introductory courses on adult education, it covers topics such as social justice; diversity and marginalization; human resource development; lifelong learning; globalization; the role of mass media and popular culture; technology; and heath, welfare, and environment, all within the context of adult education.'--
Includes bibliographical references and indexes.
Keywords: Adult education -- United States